Spontaneous degradation of methylene blue adsorbed on magnetic biochars - Anton Zubrik; Dávid Jáger; Eva Mačingová; Marek Matik; Slavomír Hredzák (Scientific Reports, 2023)
Abstract Methylene blue (MB) is one of the most widely studied organic molecules in the treatment of wastewater. Sorption, biodegradation, photodegradation, electrochemical oxidation, ozonation, and other advanced oxidative processes are frequently used to remove this dye from water solutions. The unexpected degradation of MB adsorbed on magnetic biochar from aqueous solution was observed. We found that the conditions of handling, such as drying temperature and storage period, substantially influenced the stability of the dye fixed on the (magnetic) carbon adsorbents. Twelve substances were identified by mass spectrometry as products of decomposition, mostly demethylated, oxidated, and hydroxylated substances. The decomposition of MB was further investigated using non-magnetic carbon biochars and aluminosilicate mineral zeolite. Our findings of the spontaneous decomposition of MB and the identification of the species of degradation offer a new approach to evaluate the mechanism of adsorption, the process of regeneration, and the toxicity of treated solutions.